2002
DOI: 10.1159/000066624
|View full text |Cite
|
Sign up to set email alerts
|

Steroid Receptor Coactivator SRC-1 Exhibits High Expression in Steroid-Sensitive Brain Areas Regulating Reproductive Behaviors in the Quail Brain

Abstract: The steroid receptor coactivator SRC-1 modulates ligand-dependent transactivation of several nuclear receptors, including the receptors for sex steroid hormones. Reducing the expression of SRC-1 by injection of specific antisense oligonucleotides markedly inhibits the effects of estrogens of the sexual differentiation of brain and behavior in rats and inhibits the activation of female sexual behavior in adult female rats. SRC-1 thus appears to be involved in both the development and activation of sexual behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 86 publications
2
22
0
Order By: Relevance
“…1b, f, 2b), which is consistent with other limited studies of SRC-1 mRNA in mice [59,79]. In addition, the present findings of SRC-1 expression in mouse brain are consistent with previous studies in rats [48,49,50,51,52,53,54,70,80] and birds [57,81]. SRC2-IR cells were detected throughout the mouse hippocampus, amygdala (data not shown) and hypothalamus, including the VMN, ARC and MPA (fig.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…1b, f, 2b), which is consistent with other limited studies of SRC-1 mRNA in mice [59,79]. In addition, the present findings of SRC-1 expression in mouse brain are consistent with previous studies in rats [48,49,50,51,52,53,54,70,80] and birds [57,81]. SRC2-IR cells were detected throughout the mouse hippocampus, amygdala (data not shown) and hypothalamus, including the VMN, ARC and MPA (fig.…”
Section: Resultssupporting
confidence: 93%
“…Recent work reveals that two members of this p160 family of coactivators, SRC-1 and SRC-2, are important for hormone action in brain and behavior [46,47]. SRC-1 [48,49,50,51,52,53,54,55,56,57] and SRC-2 [58,59,60] are expressed at high levels in the cortex, hypothalamus and hippocampus of rodents. Our laboratory and others have found that SRC-1 and SRC-2 are important for hormone-dependent sexual differentiation of the brain [53], gene expression in brain [54,61,62,63] and sexual behavior [54,61,62,63,64].…”
Section: Introductionmentioning
confidence: 99%
“…In the female brain, it has been found that SRC-1 plays a role in the regulation of female sexual behavior and reproductive functions [38,39,40,41], acute stress [42] and the defeminizing actions of estradiol [20], HPA axis and thyroid function [28,43,44]. The temporal distribution pattern of hippocampal SRC-1 is highly in agreement with that of our studies of hippocampal PSD-95 [45], suggesting that it may be involved in some important functions that are based on this postsynaptic protein, because PSD-95 is important in synaptic plasticity, learning and memory [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, NCOAs are overexpressed in some endocrine-dependent organs and tumors and enhance cell proliferation and differentiation (Sarvilinna et al 2006, Mukherjee et al 2007, indicating an important pathophysiological role. Also, coactivator expression is known to be sexually dimorphic (Auger et al 2002, Charlier et al 2002, Duncan & Carruth 2007 and regulated by steroid hormones (Murphy & Segal 1997, Mitev et al 2003, Charlier et al 2006. However, there are limited data regarding the expression of coregulators in the bovine ovary (Hlaing et al 2001), and no studies have been performed to investigate protein localization in different ovarian compartments.…”
Section: Introductionmentioning
confidence: 99%